Aneta Petrova. Funerary Reliefs from the West Pontic Area (6th-1st Centuries BC) (Colloquia Antiqua 14). - Damyanov, Margarit (Journal of Greek Archaeology, 2018)
Aneta Petrova’s book is a most welcome contribution to research on the Greek colonies on the West Pontic coast. Based on her doctoral dissertation defended in 2005, it brings together all known funerary monuments with figured relief decoration from the region. To my knowledge, the archaeological investigations in the last decade or so have not added new specimens – at least not from present-day Bulgaria, where large-scale excavations have been conducted in the necropoleis of Apollonia and Mesambria.